Anisotropic Stiffness Adhesives for High Shear Forces on Soft Substrates. Issue 22 (5th October 2020) - van Assenbergh, P.; Haring, Frank; Dijksman, Joshua A.; Dodou, Dimitra
Abstract: Reversible attachment on soft substrates is useful in a range of applications, including soft robotics and soft‐tissue surgical instrumentation. On rigid substrates, the use of micropatterned adhesives has been extensively explored. It has been shown that surface micropatterns provide conformability, thereby enabling the formation and preservation of contact with the substrate. On soft, deformable substrates, on the other hand, surface micropatterns largely lose their functionality. Alternative mechanisms have to be explored to maximize conformability and thus formation and preservation of contact on soft substrates. 3D‐printing is used to fabricate adhesives with internal cylindrical pores of various configurations leading to different combinations of high/low normal/shearing stiffness, and shear forces are measured on glass and on soft elastomeric substrates. On the glass substrate, shear forces are highest for the adhesives with the lowest normal stiffness, independently from their shear stiffness. On the soft substrates, the highest shear forces are achieved for the adhesives combining low normal stiffness, enabling contact formation, with high shear stiffness, promoting contact preservation. The beneficial effect of such anisotropic stiffness on shear forces increased with the deformability of the substrate. Abstract : 3D‐printing is used to fabricate a series of anisotropic adhesives with internal cylindrical pores of various configurations leading to different combinations of high/low normal/shearing stiffness and measured shear forces on glass and on soft elastomeric substrates. The beneficial effect of such anisotropic stiffness on shear forces increased with the deformability of the substrate.